Budesonide–formoterol reliever therapy in intermittent versus mild persistent asthma. Issue 2 (18th February 2021) - Papi, Alberto; Braithwaite, Irene; Ebmeier, Stefan; Hancox, Robert J.; Harrison, Tim; Holliday, Mark; Houghton, Claire; Morandi, Luca; Oldfield, Karen; Pavord, Ian D.; Reddel, Helen K.; Williams, Mathew; et al.
Traditional asthma maintenance therapy in adults and adolescents comprises inhaled corticosteroids (ICS), with a long-acting β2 -agonist (LABA) added if ICS monotherapy provides insufficient control [1, 2]. For patients with symptoms occurring on two or fewer occasions per week (so-called "intermittent" asthma [2]), who may represent around one-third of the asthma population [3], many guidelines still recommend short-acting β2 -agonist (SABA) rescue medication alone [2, 4]. These post hoc analyses of NovelSTART provide the first evidence that the exacerbation risk reduction with budesonide–formoterol reliever therapy versus salbutamol reliever therapy is similar in adults with intermittent and mild persistent asthma https://bit.ly/3iiRKqR